Respuesta :
Answer:
No.
Step-by-step explanation:
Take the second expression: 5(2 - 20)
To solve, you must distribute the 5 to all terms within the parenthesis:
5(2 - 20) = (5 * 2) - (5 * 20) = 10 - 100 = -90
On the other hand:
10 - 20 = -10
∴ the two expressions are not equivalent.
[tex]\huge\text{Hey there!}[/tex]
[tex]\large\text{\bold{No, they are not equivalent because...}}\\\\\\\large\textsf{5(2 - 20)}\\\large\textsf{= 5(2) + 5(-20)}\\\large\textsf{= 10 - 90}\\\boxed{\large\textsf{= \bf -90}}\\\\\large\textsf{10 - 20}\\\large\textsf{\boxed{\large\textsf{= \bf -10}}}\\\\\\\large\boxed{\star}\large\textsf{-10}\neq\large\textsf{-90}\large\boxed{\star}[/tex]
[tex]\huge\boxed{\mathsf{Answer: \bold{NO,}\ because \ \bf -10 \ does \ NOT}}\\\huge\boxed{\mathsf{\bf equal \ to -90}}\huge\checkmark[/tex]
[tex]\bullet\ \frak{Random\ fact: negatives \ are \ on\ the\bf \ LEFT\ side\ of\ the \ number\ line\ \& \ positives}\\\frak{are\ on\ the\bf \ RIGHT\ side\ of\ the\ number\ line}[/tex]
[tex]\large\text{Good luck on your assignment \& enjoy your day!}\\\\\\\huge\boxed{\frak{Amphitrite1040}}[/tex]